PERSONAL QUALITY AND TQM THE USE OF PERSONAL CHECKLISTS TO FACILITATE TQM - Rania Karam (European Scientific Journal, ESJ, 2014)
Unless quality is internalized at the personal level, it will never become rooted in the culture of an organization. Therefore, quality must start at a personal level. Employees who embrace quality as a personal value, often go beyond what they are asked or normally expected to do in order to reach a difficult goal or provide extraordinary service to a customer, leading to Total Quality at the workplace. However, no known studies in Lebanon were conducted to investigate the importance and implications of personal quality and personal checklists at the workplace. This survey studied the attitude of the administrative middle managers in Lebanon toward the importance and implications of personal quality, in general, and the use of personal checklists to facilitate TQM, in particular. The researcher conducted an exploratory survey using a 9–item questionnaire with middle level managers. The researcher concluded that the attitude of the administrative middle managers in Lebanon towards the importance and implications of personal quality can be considered positive in general, and that those mangers admitted that the use of the personal checklist can facilitate TQM or can be considered a tool to apply TQM at the workplace.